2012
DOI: 10.1002/hep.25873
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs in exosomes indicate hepatocyte injury and inflammation in alcoholic, drug-induced, and inflammatory liver diseases

Abstract: MicroRNAs are fine tuners of diverse biological responses and are expressed in various cell types of the liver. Here we hypothesized that circulating microRNAs (miRNAs) may serve as biomarkers of liver damage and inflammation. We studied miRNA-122 that is abundant in hepatocytes and miR-155, -146a and -125b that regulate inflammation in immune cells in mouse models of alcoholic liver disease (ALD), drug (acetaminophen; APAP)-induced liver injury (DILI), and Toll-like receptor (TLR) 9+4 ligands-induced inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
520
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 583 publications
(549 citation statements)
references
References 39 publications
25
520
0
4
Order By: Relevance
“…115 A profound increase was found in serum miR-122 levels in alcohol-fed mice with a linear correlation between serum ALT and serum miR-122 levels. 21 MiR-27b, miR-214, miR199a-3p, miR-182, miR-183, miR-200a, and miR-322 were found to be down-regulated, whereas miR-705 and miR-1224 were increased after 4 weeks of alcohol feeding in mice. 116 Alcohol has been shown to down-regulate miR-199 in rat liver sinusoidal endothelial cells and human endothelial cells.…”
Section: Alcoholic Liver Disease (Ald)mentioning
confidence: 89%
See 2 more Smart Citations
“…115 A profound increase was found in serum miR-122 levels in alcohol-fed mice with a linear correlation between serum ALT and serum miR-122 levels. 21 MiR-27b, miR-214, miR199a-3p, miR-182, miR-183, miR-200a, and miR-322 were found to be down-regulated, whereas miR-705 and miR-1224 were increased after 4 weeks of alcohol feeding in mice. 116 Alcohol has been shown to down-regulate miR-199 in rat liver sinusoidal endothelial cells and human endothelial cells.…”
Section: Alcoholic Liver Disease (Ald)mentioning
confidence: 89%
“…18 Acetaminophen administration results in increased miR-122, miR-155, miR-125b and miR-146a levels and these signatures could potentially represent biomarkers of acetaminopheninduced liver injury. 21 MiR-122 and -192 are shown to exhibit dose and exposure dependent changes in plasma parallel to aminotransferases and hepatocellular damage. 18 They were not only found to be significantly higher but also detected earlier in patients with acetaminopheninduced liver injury as compared with healthy controls.…”
Section: Drug Induced Liver Injury (Dili)mentioning
confidence: 98%
See 1 more Smart Citation
“…Exclusion criteria included diagnosis of a chronic inflammatory condition (e.g diabetes mellitus and cardiovascular diseases or recent consumption of anti-inflammatory medications (e.g ibuprofen). Since the scope of the study is to study the variation found in the levels of exosomes or their concentration in healthy individuals, therefore the indication of any inflammatory condition refers to the natural increase in the concentration of exosomes and any proteins that are associated with anti-inflammatory response [20]. Moreover, subjects were excluded if they had any pathology known to influence immune response (e.g.…”
Section: Participantsmentioning
confidence: 99%
“…Although extracellular vesicles can be isolated using methods such as filtration concentration, flotation density gradients and immunocapture beads, the most widely used method is successive centrifugation followed by ultracentrifugation (UC) (23,24). Extracellular vesicles are known to be involved in myriad cellular processes including coagulation (25), inflammation (26), tumor progression (27), immune response regulation (28), ectodomain shedding of membrane proteins (29), antigen presentation (30), intracellular communication (31), transfer of RNA and proteins (32) and transfer of infectious cargo (prions and retroviruses) (33,34). In addition, extracellular vesicles have been implicated in the pathogenesis of vascular disorders (35,36), cancers (37,38), diabetes (39) and infectious diseases (40,41).…”
mentioning
confidence: 99%